[FeFe]‐Hydrogenase with Chalcogenide Substitutions at the H‐Cluster Maintains Full H2 Evolution Activity. Issue 29 (23rd May 2016) - Noth, Jens; Esselborn, Julian; Güldenhaupt, Jörn; Brünje, Annika; Sawyer, Anne; Apfel, Ulf‐Peter; Gerwert, Klaus; Hofmann, Eckhard; Winkler, Martin; Happe, Thomas
Abstract: The [FeFe]‐hydrogenase HYDA1 from Chlamydomonas reinhardtii is particularly amenable to biochemical and biophysical characterization because the H‐cluster in the active site is the only inorganic cofactor present. Herein, we present the complete chemical incorporation of the H‐cluster into the HYDA1‐apoprotein scaffold and, furthermore, the successful replacement of sulfur in the native [4FeH ] cluster with selenium. The crystal structure of the reconstituted pre‐mature HYDA1[4Fe4Se]H protein was determined, and a catalytically intact artificial H‐cluster variant was generated upon in vitro maturation. Full hydrogen evolution activity as well as native‐like composition and behavior of the redesigned enzyme were verified through kinetic assays, FTIR spectroscopy, and X‐ray structure analysis. These findings reveal that even a bioinorganic active site with exceptional complexity can exhibit a surprising level of compositional plasticity. Abstract : Cofactor swapping : The complex catalytic cofactor of [FeFe]‐hydrogenases (H‐cluster) exhibits an unexpected level of compositional plasticity. The complete chemical incorporation of an H‐cluster analogue into HYDA1 from C. reinhardtii with chalcogenide replacement in the cubane subcluster yields an enzyme variant with full catalytic H2 ‐production activity.